NEET Youth in Austria - Extent, Economic Costs and Recommendations - Bacher, Johann (Momentum Quarterly, 2020)
The NEET indicator has become an integral part of social reporting and serves as a benchmark for social, labor and educational policy measures. The article examines the NEET (Not in education, employment or training) risk in Austria in 2018 and presents statistical relationships. In addition, the economic costs of NEET are estimated. Finally, recommendations for action are derived from previous research on NEET. A short conclusion with reference to the current program of the new federal government concludes the contribution.